Drug delivery system based on an antibacterial layer-by-layer coating on urinary catheters: an experimental and simulation approach - Pulido, Ruth; Naveas, Nelson; Fernández-Alonso, Francisco Javier; Manso-Silván, Miguel; Soriano, Leonardo; Torres-Ulloa, Carlos; Mena-Ulecia, Karel; Recio-Sánchez, Gonzalo; Garcia-Sandoval, Juan Paulo; Hernández-Montelongo, Jacobo (Frontiers in Bioengineering and Biotechnology, 2025)
Urinary catheters (UCs) are critical in biomedical applications, but prolonged use increases the risk of catheter-associated urinary tract infections (CAUTIs), a leading cause of healthcare-associated infections (HAIs). The present study presents a dual strategy to create an antibacterial surface on commercial Foley silicone UCs by combining a contact-killing effect with the controlled release of antimicrobial compounds. We designed a drug delivery system using a layer-by-layer (LbL) antibacterial coating of carboxymethylcellulose (CMC) and chitosan-silver (CHI-Ag) complexes, with ciprofloxacin (CFX) as the model drug. The resulting LbL coating, about 1 μm thick, incorporated Ag0 and demonstrated a high capacity for CFX loading, releasing over twice the amount (70 μg/cm2) compared to uncoated UCs (30 μg/cm2). The antibacterial efficacy was significantly higher in the LbL-coated samples, particularly against S. aureus compared to E. coli. Drug release experiments, modeled using Fick’s second law, indicated a diffusivity of 1.744×10−5 cm2/h. Our mathematical model predicts how variations in drug loading and rest times impact release profiles. Finally, molecular dynamics simulations suggested strong compatibility between CFX and the LbL layers, though with relatively low stability. This dual strategy holds promise for reducing CAUTIs effectively.